Atroposelective Synthesis of 3, 3'‐Bisindoles Bearing Axial and Central Chirality: Using Isatin‐Derived Imines as Electrophiles. Issue 6 (21st April 2020) - Sheng, Feng‐Tao; Li, Zhi‐Min; Zhang, Yi‐Zhu; Sun, Li‐Xing; Zhang, Yu‐Chen; Tan, Wei; Shi, Feng
Summary of main observation and conclusion: An atroposelective synthesis of a new class of 3, 3'‐bisindoles bearing axial and central chirality has been established via catalytic asymmetric addition reactions using isatin‐derived imines as electrophiles (23 examples, up to 80% yield, > 95 : 5 dr, 98 : 2 er). This approach takes advantage of chiral phosphoric acid‐catalyzed dynamic kinetic resolution of 2‐substituted 3, 3'‐bisindoles via nucleophilic addition of such substrates with isatin‐derived imines. In this approach, isatin‐derived imines acted as a class of competent electrophiles due to their high reactivity and bulky size, which provided an easy access to axially chiral 3, 3'‐bisindoles incorporated with a biologically important chiral 3‐aminooxindole unit. This approach has greatly expanded the generality and applicability of the strategy of dynamic kinetic resolution for the synthesis of enantioenriched 3, 3'‐bisindole derivatives bearing both axial and central chirality. Abstract : An atroposelective synthesis of 3, 3'‐bisindoles bearing axial and central chirality has been established via catalytic asymmetric addition reactions using isatin‐derived imines as electrophiles.